Pengaruh Pengetahuan Akuntansi, Skala Usaha dan Ketidakpastian Lingkungan Terhadap Penggunaan Informasi Akuntansi (Studi Kasus UMKM Sulaman Kecamatan Pariaman Utara) - Sulastri; Arivetullatif (Jurnal Ekonomi dan Bisnis Digital, 2023)
This research aims to analyze the influence of accounting knowledge, business scale and environmental uncertainty on the use of accounting information in Sulaman Naras MSMEs. This research uses descriptive analytical research with a quantitative approach. The sampling method used in the research was purposive sampling, so that a sample of 61 respondents was obtained. The data analysis used was multiple linear regression using the SPSS version 26 program. From the results of the regression test, it was found that there was an influence of accounting knowledge on the use of accounting information, business scale had an influence on the use of accounting information, environmental uncertainty had an influence on the use of accounting information. Accounting knowledge, business scale and environmental uncertainty influence the use of accounting information, based on the Adjust R Square value of 0.614, indicating that the contribution of the variables accounting knowledge, business scale and environmental uncertainty to the use of accounting information is 0.714 or 71.4% while the remaining is 28.6 % is determined by other variables not analyzed in the model in this study.